PELOPHYLAX TERENTIEVI (MEZHZHERIN, 1992) (RANIDAE, PELOPHYLAX)NING GELMINTLARI FAUNASI - Aliyev Sh.T. , Aliyev Sh.T.; Amirov O.O., Amirov O.O. (Actual problems and prospects of the study of the fauna, 2024)
In this research work, all the helminths recorded in P. terentievi (Mezhzherin, 1992) found in the regions of southern Uzbekistan (Kashkadarya and Surkhondarya regions) were taxonomically analyzed, invasion extensiveness and intensity, abundance and dominance indices were presented. The helminth fauna of P. terentievi found in Uzbekistan is explained by the composition of Plathelminthes Schneider, 1873 type - 18 species, Acanthocephala Rudolphi, 1808 type - 6 species, Nematoda Rudolphi, 1808 type - 10 species.